Psychosocial work environment, work engagement, and employee commitment: A moderated, mediation model - Teo, Stephen T.T.; Bentley, Tim; Nguyen, Diep (International journal of hospitality management, 2020)
•Workplace bullying was found to be prevalent in the US hospitality sector.•Work engagement was found to be a full mediator of the relationships between HPWS, POS, and affective commitment.•Workplace bullying mediated the relationship between HPWS and affective commitment, while psychosocial safety climate moderated this mediating impact. This paper contributes to the growing body of literature on the wellbeing of hospitality employees from a perspective of strategic human resource management. The role of high performance work systems (HPWS) in enhancing the affective commitment of hospitality employees is examined. The study found work engagement to mediate the relationships between HPWS, perceived organizational support, and affective commitment. Workplace bullying, a highly prevalent phenomenon in the hospitality sector, was found to mediate the relationship between HPWS and affective commitment, while psychosocial safety climate moderated this mediating impact. We will suggest the implications for managing psychosocial work hazards in hospitality organizations.